Dimensions of informal care in Greece: the family's contribution to the care of patients hospitalized in an oncology hospital - Sapountzi-Krepia, Despina; Psychogiou, Maria; Sakellari, Evanthia; Toris, Anastasios; Vrettos, Anargyros; Arsenos, Panagiotis; Raftopoulos, Vasilios (My University, 2008)
Aims and objectives. This study aims to explore the kind and frequency of care provided to hospitalized cancer patients by relatives and the reasons for providing this care. Background. Informal care is a common phenomenon across many countries. In Greece, informal caring activities occur in most hospitals. Patients' relatives stay by their bedside for long hours and assist with care. This phenomenon is highly correlated with the nursing staff shortage. Method. This study was carried out in a Greek oncology hospital. The sample consisted of 150 informal caregivers. We used a 37-item questionnaire called In-Hospital Informal Care Questionnaire Acute Care. Results. The participants provide substantial help to their patients daily. On average, they stay by their bedside for 20·23 hours in a 24-hour period. Additionally, 104 participants stated that they hire a privately paid patient's helper. The relatives stay by their patients' bedside for various reasons such as: (1) severity of the condition; (2) providing psychological support; (3) family tradition; (4) because they do not believe their patients are safe in the hospital without their supervision; or (5) the nursing staff shortage. Conclusions. The participants offer informal care that reflects specific nursing duties. We could argue that Greek hospitals 'use' relatives as unpaid labour to compensate for the nursing shortage. It is disquieting that usually someone from the hospital staff suggests to the relatives to stay at the patient's bedside even after visiting hours or to hire a private paid patient's helper. This implies that the staff considers such contribution necessary. Relevance to clinical practice. The findings show that relatives perform daily tasks that nurses should be performing. They indicate that the hospital should introduce specific staffing policies for reducing families' burden. Our findings could influence future staffing plans of nursing managers, policy makers or health authorities.
Keywords: Cancer; Family; Greece; Nursing; Nurses; Informal care